Taxonomic And Nomenclatural Notes On Malesian Araceae I — Resolving Homalomena ovata, and a new name in Homalomena for Chamaecladon ovatum - Sin Yeng, Wong; Peter C., Boyce (International Aroid Society, Inc., 2022)
Corrections and updates are made to the taxonomy and nomenclature of Homalomena ovata Engl., Homalomena borneensis Ridl, and Chamaeclason ovatum Schott. Homalomena hostifolia Engl. is treated as a homotypic superfluous name for H. ovata Engl. Homalomena ovatum (Schott) Hook.f., an illegitimate name, is renamed Homalomena nathanielii and treated as a Singapore endemic in the Homalomena Griffithii complex